Import Quotas and the Product Cycle - Dollar, David (Quarterly Journal of Economics, 1987)
This paper uses a dynamic general equilibrium model of the product cycle in North-South trade to analyze the short-run and long-run effects of import quotas imposed in the North on manufactured goods from the South. The short-run effects are predictable: real wages in the North may rise as a result of the protection, though even this is not certain if the South captures the quota rents. The long-run effect of the protection is to unambiguously reduce real wages in the North because the quotas artificially increase production costs in the North relative to the South, accelerating the transfer of technology and capital from North to South.